2021
DOI: 10.1021/acs.jpcc.1c01823
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Agglomeration of Supported Metal Clusters Induced by High-Flux X-ray Absorption Spectroscopy Measurements

Abstract: Supported metal clusters are widely used in catalysis for many important reactions. To understand the catalytic properties, in situ/operando characterization techniques, such as X-ray absorption spectroscopy (XAS), provide essential details of the size, shape, and chemical composition of the cluster and the nature of the active sites. New-generation synchrotrons combined with focusing beamlines provide high-flux-density X-rays for improved detection sensitivity as well as higher time and spatial resolution. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…However, it is possible that the high intensity X-ray beam may induce the formation of additional metallic Ni; therefore, this value likely represents an upper limit to the amount of metallic Ni formed. 36 Wavelet transform analysis was performed on the EXAFS (Figure S7 37 Another calculation was carried out to determine the number of atoms in a particle that would represent the CNs extracted from the EXAFS fitting (see details in the Supporting Information). 38 The calculation indicates that the CN values from the EXAFS fit correspond to a particle of 40−100 atoms.…”
Section: ■ Resultsmentioning
confidence: 99%
“…However, it is possible that the high intensity X-ray beam may induce the formation of additional metallic Ni; therefore, this value likely represents an upper limit to the amount of metallic Ni formed. 36 Wavelet transform analysis was performed on the EXAFS (Figure S7 37 Another calculation was carried out to determine the number of atoms in a particle that would represent the CNs extracted from the EXAFS fitting (see details in the Supporting Information). 38 The calculation indicates that the CN values from the EXAFS fit correspond to a particle of 40−100 atoms.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Significant beam-induced reduction and agglomeration is also shown for Ni supported on beta zeolite during in situ reduction at an intermediate-flux-density, indicating that beam-induced changes in heterogeneous catalysts could be common at intermediate- and high-flux-density beamlines. 166…”
Section: Structure and Reshapingmentioning
confidence: 99%
“…Newton et al 27 investigated a Cu(II)-containing zeolite in heterogeneously catalyzed methane oxidation to methanol and found that Cu(II) may undergo reduction in the presence of methane or pure helium upon X-ray irradiation. Albrahim et al 28 investigated a highly dispersed RhO x /Al 2 O 3 catalyst by in situ XAS and detected that rhodium clusters undergo reduction even at room temperature in the presence of hydrogen and intense X-rays; in situ heating to 310 1C leads to further agglomeration of clusters, comparable to agglomeration typically observed at 650 1C without exposure to the X-ray beam. Van Schooneveld and DeBeer 29 showed that iron in K 3 [Fe(CN) 6 ] and manganese in KMnO 4 can undergo X-ray-induced reduction during XAS measurements; the authors investigated the relationship between the X-ray dose and the extent of metal reduction by measuring these samples at different synchrotron beamlines.…”
Section: Introductionmentioning
confidence: 98%